SEDIAAN SABUN MANDI PADAT DAUN SIRIH MERAH (Piper crocatum) KOMBINASI SERAI (Cyombopogo citrus) ASAL DESA LAINUNGAN KABUPATEN SIDRAP - Rahmasiah Rahmasiah; Sulaeman; Reny Anggrany; NurulNisa (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2023)
red betel leaf (piper crocatum) is a native Peruvian plant, then spread to several regions in the world including Indonesia. This research was to find out whether red betel leaf extract (piper crocatum) and citronella oil (Cyombopogo citrus) can be made into solid bath soaps. This research is an experimental research, where red betel leaf extract (piper crocatum) and citronella oil (Cyombopogo citrus) with different formulations, namely concentrations of 10%, 15% and 20%. using 70% ethanol solvent and using the maceration method for 5 days then in the evaporator and red betel leaf extract is formed. The results of the study showed that the administration of solid bath soap can be made with a concentration of 10%, 15% and 20%.